Pendampingan Pembuatan Media Pembelajaran Berbasis Aplikasi Canva Bagi Guru SMP Srijaya Negara: Assistance for Making Learning Media Based on Canva for Teacher in Srijaya Negara Junior High School - Sulkipani Sulkipani; Edwin Nurdiansyah; Camellia Camellia; Aulia Novemy Dhita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Community service activities carried out on this occasion are related to improving teacher competence based on Law No. 14 of 2005 concerning Teachers and Lecturers. The method of community service is mentoring the teachers of Srijaya Negara Junior High School. The service results showed increased understanding and ability of the Teachers of Srijaya Negara Junior High School to make Canva-based learning media. Mentoring activities for making Canva-based learning media went well and efficiently. The teachers showed enthusiasm for creating learning media using Canva. The enthusiastic attitude of the teachers can be seen from the enthusiasm and desire to complete Canva-based learning media. In addition, the understanding and knowledge of teachers in utilizing Canva to create learning media can be seen from the initial test (pre-test) and the final test (post-test).